Evaluasi Efektivitas Pengelolaan Limbah Covid-19 di RSKD Duren Sawit - Ekaputri, Sesharia Yenita; Sulistiyorini, Desy; Sutanto, Finka Reztya (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: During this pandemic, hospitals, as healthcare providers, play a central role in generating the largest amount of Covid-19 waste compared to other healthcare facilities, especially when the hospital is designated as a Covid-19 referral hospital. This study was conducted to analyze the management of Covid-19 waste at the RSKD Duren Sawit, focusing on the stages of waste management, waste characteristics, facilities and infrastructure, as well as administrative aspects involved in Covid-19 waste management at RSKD Duren Sawit. Methods: This research was carried out using a qualitative study design to gain an in-depth understanding of Covid-19 waste management at the Special Regional Hospital (RSKD) Duren Sawit. Data collection was conducted through in-depth interviews with informants, consisting of key informants, primary informants, and additional informants. A total of four respondents were selected based on specific criteria relevant to the research topic. These interviews aimed to explore various perspectives and experiences related to the procedures and challenges of medical waste management during the pandemic, to obtain comprehensive information on the implementation of policies and practices in waste management at RSKD Duren Sawit. Results: The findings of this study indicate that Covid-19 waste management at RSKD Duren Sawit consists of disinfection, packaging, waste delivery to the Temporary Hazardous Waste Management Facility, weighing, transportation by a licensed transporter, and eventual incineration by a third party with appropriate permits. The Covid-19 waste includes food and beverage waste from patients, infectious waste from medical procedures, personal protective equipment (PPE) used by staff, and other items contaminated with the Covid-19 virus. Conclusion: The facilities and infrastructure for waste management at RSKD Duren Sawit need further enhancement; however, overall, they do not hinder the Covid-19 waste management process. The Covid-19 waste management process at RSKD Duren Sawit is in accordance with regulations, although there are still challenges encountered on the ground. Additionally, there is a need for hospital policies related to Covid-19 waste management to ensure that the implementation of waste management at RSKD Duren Sawit can be carried out more efficiently. Keywords: Waste management ; Covid-19 ; hospital